TAPAKAN BARON NAWA SANGGHA PURA PUNCAK PADANG DAWA DALAM UPACARA RUWAT BUMI - Dana, I Wayan (Acintya, 2010)
Tapakan Barong Nawa Sanggha is not only gloriï¬ed in Pura Pucak Padang Dawa but also can be foundÂ in Para Natar Sari Apuan and Puro Pucak Kembar Pucung Baturiti, Tabanan.The three tapakan, inÂ accordance to calculation time boxed on Bali calendar, by turns. conduct the ritual ceremony ngelawarig.Â melelungan. or ngunya amund the various area.\' of Central Bali as the fonn of Ruwat Bumi ceremony. TheÂ ceremony of Ruwat Bumi is an unseparable part of â€˜panca yadnya â€™( the ï¬ve holy victims) executed honestlyÂ by Hindu society. Tapokan Bamng Nawa Sanggha becomes a media in the ceremony because tapakanxymbolically master: and guards the power from all xides of point. The form of nine barong shows theÂ pawerfmm all sides which is believed by the society to have God power that is able to purify the worldÂ from threatening dangen For the reason, the bamng is mostly waited for by the society in order to getpeaceï¬d and harmonious life forever:Keyword: Tapakan Barong Nawa Sanggha. Paruman Barong, Pucak Padang Dawa, Ruwat Bumi Ceremony